2018
DOI: 10.4274/jcrpe.5119
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide Study of Turner Syndrome in Ukrainian Children: Prevalence, Genetic Variants and Phenotypic Features

Abstract: Objective: We aimed to investigate the prevalence of Turner syndrome (TS) in the Ukrainian population, the frequency of karyotype variants, the age of children at diagnosis, the degree of short stature and phenotypic features in TS girls.Methods: A retrospective analysis was made in 538 TS girls aged 0.11-18.2 years within the time period of 2005-2015 with detailed examination of 150 patients.Results: The prevalence of TS in Ukraine is 77.5 in 100.000 live female births. The average age at diagnosis is 9.33±4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 45 publications
1
10
1
6
Order By: Relevance
“…Microcephaly is uncommon in TS, and only a few cases with this finding have been reported in the literature. 26 Regarding body weight, our patients' BMI was higher than that found in a national study in Ukraine, 27 in which 13.8% of the patients were found to be overweight and 6.9%, obese. In our study, 18.5% and 33.3% of the patients were overweight and obese, respectively.…”
Section: Discussioncontrasting
confidence: 64%
“…Microcephaly is uncommon in TS, and only a few cases with this finding have been reported in the literature. 26 Regarding body weight, our patients' BMI was higher than that found in a national study in Ukraine, 27 in which 13.8% of the patients were found to be overweight and 6.9%, obese. In our study, 18.5% and 33.3% of the patients were overweight and obese, respectively.…”
Section: Discussioncontrasting
confidence: 64%
“…The earliest and largest studies which included patients from the 1960s demonstrated median ages of diagnosis from 14.5 to 15.1 years (Berglund et al, 2019; Schoemaker et al, 2008; Stochholm et al, 2006). More recently a study published in 2018 reported an average age of 9.3 years in a cohort of over 500 girls with TS (Zelinska et al, 2018). However, two previous studies reported similar age distributions as ours, but were based on much smaller cohorts—about a third in size (Apperley et al, 2018; Sävendahl & Davenport, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Massa & Vanderschueren-Lodeweyckx, 1991; Noordman et al, 2019;Saikia et al, 2017;Sävendahl & Davenport, 2000;Schoemaker et al, 2008;Simm et al, 2008;Stochholm et al, 2006;Yes ¸ilkaya et al, 2015;Zelinska et al, 2018). Average or median age range was 4.2-18.0 years.…”
mentioning
confidence: 99%
“…Es llamativo que, en el presente estudio, el grupo de ST por anomalías estructurales puras o en variedad mosaico se diagnosticó más temprano que el resto de los grupos, ya que descripciones realizadas por otros autores, como González y Sepúlveda 13 , señalan que el diagnóstico clínico de ST es sesgado en los casos que no son 45,X porque las características fenotípicas no son muy evidentes. También el estudio de Zelinska et al 14 muestra una edad de diagnóstico más temprana en el grupo de pacientes con monosomía pura que en aquellas con anomalías estructurales. En nuestro estudio, el resultado es singular y puede estar en relación a las características de la muestra estudiada o a la presencia de variantes estructurales que incluyeron duplicaciones, deleciones Xp, marcadores y el frecuente isocromosoma Xq.…”
Section: Discussionunclassified